From Crisis to Stability: How Macroeconomics Shapes Islamic Banking and MSME Futures? - Nasution, Akmal Huda; Fakhri, Ulumuddin Nurul (Share: Jurnal Ekonomi dan Keuangan Islam, 2024)
This study examines the impact of the COVID-19 pandemic on the nexus between macroeconomic conditions, Islamic banking performance, and MSME financing in Indonesia. Utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM) and secondary data spanning January 2020 to June 2023, the research analyzes the direct effects of macroeconomic factors on both the financial performance of Islamic banks and the provision of financing to MSMEs.  The findings indicate a statistically significant positive relationship between macroeconomic stability and both Islamic banking financial performance and MSME financing. Conversely, the study reveals no statistically significant relationship between the financial performance of Islamic banks and the scale of MSME financing during the period. These results underscore the critical role of macroeconomic stability as a primary determinant of financial performance for both Islamic banks and MSMEs, particularly during periods of economic crisis.========================================================================================================ABSTRAK – Dari Krisis ke Stabilitas: Bagaimana Makroekonomi Membentuk Masa Depan Perbankan Syariah dan UMKM? Penelitian ini mengkaji dampak pandemi COVID-19 terhadap keterkaitan antara kondisi makroekonomi, kinerja perbankan syariah, dan pembiayaan UMKM di Indonesia. Menggunakan metode Partial Least Squares Structural Equation Modeling (PLS-SEM) dan data sekunder yang mencakup periode Januari 2020 - Juni 2023, penelitian ini menganalisis pengaruh langsung faktor-faktor makroekonomi terhadap kinerja keuangan bank syariah dan penyediaan pembiayaan kepada UMKM. Hasil penelitian mengindikasikan adanya hubungan positif yang signifikan secara statistik antara stabilitas makroekonomi dengan kinerja keuangan perbankan syariah dan pembiayaan UMKM. Sebaliknya, studi ini tidak menemukan hubungan yang signifikan secara statistik antara kinerja keuangan perbankan syariah dengan skala pembiayaan UMKM periode tersebut. Temuan ini menekankan pentingnya stabilitas makroekonomi sebagai penentu utama kinerja keuangan, baik bagi bank syariah maupun UMKM, terutama dalam masa-masa krisis.